2001
DOI: 10.1128/iai.69.5.3255-3263.2001
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination against the Intracellular PathogensLeishmania majorandL. amazonensisby Directing CD40 Ligand to Macrophages

Abstract: CD40 ligand (CD40L) is a potent inducer of interleukin-12 (IL-12) production from macrophages and dendritic cells. We show that combining CD40L with antigen derived from Leishmania is an effective way to preferentially induce type 1 immune responses to the antigen and to vaccinate mice against subsequent challenge with virulent organisms. Mice vaccinated in this way had smaller lesions, with more than 1,000-fold fewer parasites within them. To improve the efficiency of CD40L-induced immunopotentiation, we atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 52 publications
1
15
0
1
Order By: Relevance
“…The same thing was reported by Rolph and Kaufmann (2001), Chen et al (2001) and Field et al (2007) which uses a combination of CD40 and vaccine of heat-killed Listeria mononcytogenes and Leishmania major. The development of vaccines based on cell-mediated immunity was also reported by Lawrence et al (2012) in a vaccination using HKSA.…”
Section: Vaccination Based On Cell-mediated Immunitysupporting
confidence: 69%
“…The same thing was reported by Rolph and Kaufmann (2001), Chen et al (2001) and Field et al (2007) which uses a combination of CD40 and vaccine of heat-killed Listeria mononcytogenes and Leishmania major. The development of vaccines based on cell-mediated immunity was also reported by Lawrence et al (2012) in a vaccination using HKSA.…”
Section: Vaccination Based On Cell-mediated Immunitysupporting
confidence: 69%
“…(4,20,31,41). Previously, we have shown that combining CD40L with leishmanial antigens can improve disease outcome in susceptible animal models (7). Also, vaccination with CD40 ligand trimer DNA was shown to provide protection in the BALB/c host (14).…”
Section: Discussionmentioning
confidence: 99%
“…Animals that were vaccinated with wild-type or transgenic organisms were equally protected against rechallenge, indicating that these organisms, although reduced in virulence, retain immunogenicity required to induce an adaptive immune response. Previous studies in our laboratory demonstrated that the combination of L929 cells expressing CD40L with parasite antigens was able to provide significant protection in the susceptible BALB/c mouse (7). Also, CD40L trimer DNA has been used successfully to vaccinate BALB/c mice against L. major (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its role in acquired resistance in leishmaniasis is strongly supported by the ability of CD40L to potentiate vaccine-induced immunity to L. major (11,15) and by the failure of mice with induced or genetic deficiencies in CD40 engagement to control infection, which in each case was associated with impaired production of IL-12 (3,6,18,49). That CD40 ligation alone is insufficient for IL-12 production in vivo has been demonstrated in mice, which required a microbial exposure using a soluble antigen derived from Toxoplasma gondii to produce high levels of the cytokine following treatment with agonistic anti-CD40 antibodies (44).…”
Section: Discussionmentioning
confidence: 99%